2018
DOI: 10.1017/jfm.2018.866
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent alignment, tumbling and stretching of slender rods in isotropic turbulence

Abstract: We examine the dynamics of slender, rigid rods in direct numerical simulation of isotropic turbulence. The focus is on the statistics of three quantities and how they vary as rod length increases from the dissipation range to the inertial range. These quantities are (i) the steady-state rod alignment with respect to the perceived velocity gradients in the surrounding flow, (ii) the rate of rod reorientation (tumbling) and (iii) the rate at which the rod end points move apart (stretching). Under the approximati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…For fibers longer than the Kolmogorov length η, such preferential sampling of the velocity field has not been investigated in details. Pujara et al [21] showed numerically that when the fiber length L exits the viscous regime (L < η) and enters the inertial regime (L > η), the preferential orientation switches from the local vorticity to the most extensional eigenvector of the coarse-grained strain rate tensor. This could suggest that the spinning rate of a long fiber should decrease with length, as the preferential orientation with the vorticity is lost when the fiber length is in the inertial regime.…”
Section: Introductionmentioning
confidence: 99%
“…For fibers longer than the Kolmogorov length η, such preferential sampling of the velocity field has not been investigated in details. Pujara et al [21] showed numerically that when the fiber length L exits the viscous regime (L < η) and enters the inertial regime (L > η), the preferential orientation switches from the local vorticity to the most extensional eigenvector of the coarse-grained strain rate tensor. This could suggest that the spinning rate of a long fiber should decrease with length, as the preferential orientation with the vorticity is lost when the fiber length is in the inertial regime.…”
Section: Introductionmentioning
confidence: 99%
“…The Coriolis term × (I • ) is generally neglected for long fibers assuming that the spinning rate is smaller than the relaxation rate of tumbling. This disputable assumption is generally justified by the weak alignment of long fibers with coarse grained vorticity (Pujara et al, 2019). The Equation (1) then reduces to a simplified Langevin equation,…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant effort has been devoted to investigating numerically the dynamics of rigid and axisymmetric ellipsoids in homogeneous and isotropic turbulence (HIT) (Shin & Koch 2005; Ni, Ouellette & Voth 2014; Byron et al. 2015; Pujara, Voth & Variano 2019) and in turbulent channel flow (Mortensen et al. 2008; Marchioli, Fantoni & Soldati 2010; Zhao, Marchioli & Andersson 2014; Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic particles have applications in industrially relevant flows, such as in pulp and papermaking (Lundell, Söderberg & Alfredsson 2011) and environmental problems, like modelling of phytoplankton (Guasto, Rusconi & Stocker 2012;Basterretxea, Font-Munoz & Tuval 2020), sedimentation (Meiburg & Kneller 2010), aerosols (Kleinstreuer & Feng 2013), ice crystals in clouds (Kristjànsson, Edwards & Mitchell 2000;Shultz 2018;Jiang et al 2019) and micro-fibre pollution in oceans (Ross et al 2021). In recent years, significant effort has been devoted to investigating numerically the dynamics of rigid and axisymmetric ellipsoids in homogeneous and isotropic turbulence (HIT) (Shin & Koch 2005;Ni, Ouellette & Voth 2014;Byron et al 2015;Pujara, Voth & Variano 2019) and in turbulent channel flow (Mortensen et al 2008;Marchioli, Fantoni & Soldati 2010;Zhao, Marchioli & Andersson 2014;Zhao et al 2015;Challabotla, Zhao & Andersson 2015a,b;Marchioli, Zhao & Andersson 2016;Dotto & Marchioli 2019;Dotto, Soldati & Marchioli 2020). Natural fibres can have complex and non-regular shapes, difficult to systematically characterise.…”
mentioning
confidence: 99%